2003
DOI: 10.1080/0144361021000043173
|View full text |Cite
|
Sign up to set email alerts
|

A new predictor of cephalopelvic disproportion?

Abstract: Cephalopelvic disproportion (CPD) is a recognised obstetric problem with potential risk to both mother and infant. Identification of those mothers at risk of CPD is difficult and has concentrated in the past on such measurements as maternal shoe size and height. Our objective in this study was to examine new anthropomorphic parameters as indicators of CPD. This was a case controlled study of sixty consecutive women, and their partners, who had caesarean section performed for CPD and 60 case matched controls. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…Other studies have examined maternal shoe size in relation to cephalopelvic disproportion and none found a correlation between maternal shoe size and mode of delivery, which also support our fi ndings (Gorman et al 1997;Ellison and De Wet 2001;Connolly et al 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies have examined maternal shoe size in relation to cephalopelvic disproportion and none found a correlation between maternal shoe size and mode of delivery, which also support our fi ndings (Gorman et al 1997;Ellison and De Wet 2001;Connolly et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Th is is unlike the fi nding of independent association between shoe size and method of delivery by other authors (Frame et al 1985;Merchant et al 2001;Sheiner et al 2005). Our study did not fi nd any association between the fetal birth weight, head circumference and method of delivery and supports the fi ndings of other authors (Mahmood et al 1988;Connolly et al 2003;Stephens et al 2006).…”
Section: Discussionsupporting
confidence: 64%
“…In the current study, mid upper arm circumference (MUAC) was found to be insignificant predictor of cesarean delivery rate on the basis of multivariate analysis and the study agrees with the findings of Mohamed et al [21]. Previous studies have shown that MUAC well correlated with an increase in cesarean delivery rate [36][37][38][39][40][41][42][43][44][45].…”
Section: Discussionsupporting
confidence: 89%
“…1,2,5 None of these studies found a correlation between maternal shoe size and mode of delivery. Our study supports this literature because we also did not find a correlation between shoe size and mode of delivery.…”
Section: Discussionmentioning
confidence: 99%